Prevalence of Thrombocytopenia and Platelet Dysfunction in Women Delivering at a Tertiary Care Hospital and Prevalence of Platelet Abnormalities in their Neonates with Perinatal Outcomes: A Retrospective Study - Gowri, Vaidyanathan; George fenn, Miriam; Al Abri, Al Muhanad; Al Hashmi, Lubna (International Journal of Innovative Research in Medical Science, 2022)
Objective: To study the etiology and severity of platelet disorders, clinical manifestations, mode of delivery and neonatal outcome in pregnant women with thrombocytopenia and platelet dysfunction delivering in a tertiary care center in the Middle east. Methods: A retrospective cohort study was done on pregnant women admitted to Sultan Qaboos University Hospital (SQUH) from January 2011 to December 2020 with platelet abnormalities as per the registry were included. Thrombocytopenia associated with drugs, viral infection, pre-eclampsia, and HELLP syndrome were excluded. Results: Total number of deliveries were 39,522 during the study period. Of these 220 patients had thrombocytopenia and platelet abnormalities according to our inclusion criteria. The incidence of platelet abnormalities was 0.56% The mean gestational age at delivery was age 37.53 weeks. The mean platelet count was 90.41cells/dl. The highest two etiologies in this study were gestational thrombocytopenia (GT) (24.6%) and immune thrombocytopenic purpura (ITP) (22.6%). Out of 220, 9.5% were treated with prednisolone. There was a significant correlation between maternal platelet counts and medical treatment was received. No significant correlation between maternal platelet counts and mode of delivery was obtained. Nine neonates had platelet abnormalities, of which 44.4% were born to mothers with immune thrombocytopenic purpura (ITP). Mild to moderate neonatal thrombocytopenia was present in 66.6% of the neonates. 33.3% of the thrombocytopenic neonates had experienced hemorrhagic manifestations with good clinical outcome. Conclusion: The incidence of platelet abnormalities was 0.56% according to our study. ITP was more associated with severe thrombocytopenia and premature delivery.